Działalność wojenna Mieczysława Moczara (IX 1939 – I 1945) - Lesiakowski, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 1999)
The years of the World War II constituted a very important period in a political biography of Mieczylaw Moczar – „Mietek”. He was practically an unknown individual before the war, after that he became a prominent member of the party and state apparatus crated by Polish Workers Party (PPR – communists). There were several reasons of his such a quick advance. In September 1939 he left a prison in Łęczyca where he was imprisoned for his illegal political activity. Than he reached Białystok in a moment difficult to be precisely determined. The city was than situated in the Soviet occupational zone. There as „Kruk” he was engaged in secret operations of the Soviet military intelligence service. In mid 1941 the territory was occupicd by the Germans. Thus he was engaged in the organisation of the communist military-political conspiracy. Being a commander in chief of the District of People’s Guard and then People’s Army in Łódź and in Lublin region and then in Kielce region the managed the organisational and military activity of the guerrilla troops subordinated to him. It happened he took part in the clashes with the Germans personnally. The conflict between the communists and the military and political organisation of the Polish Underground State leaded the structures commanded by Moczar to the engagement in the fratricide fight against the Polish underground forces. A bitter struggle between M. Moczar and Leon Kasman („Janowski”) appointed by Moscow characterised the Moczar’s political position at that time. In spite of the risk of provoking a conflict between PPR and VKP(b) (Russian communist party) he deeply opposed the independent activity of L. Kasman. M. Moczar did not try to avoid conflicts in the years of the war. He acted brutally and with full determination. He achieved a strong position step by step. That resulted in his admission to the Central Committee of the PPR in August 1944.